Analysis of Digital Marketing Strategies in Encouraging SHaria Investment towards Economic Growth in Indonesia - Pratama, Gama; Selasi, Dini; Vidiati, Cory; Salsabila, Syafira (Journal of Islamic Economic Development, 2023)
In this modern era, the acceptance of technology and the internet in society is widespread, so it is not surprising that digital marketing activities have become the main choice in doing business. Investment is the process of allocating a number of resources, such as money, time, and effort, into an asset or project with the aim of gaining profits in the future. In making investments, we must understand the risks involved and carry out proper analysis before making a decision. This research uses a qualitative research method with a descriptive, evaluative approach. The social impacts and conditions in question are the past, present, and even future conditions. It is also related to other objects such as social, economic, and cultural, as well as history and other social sciences. Digital marketing plays a very important role in introducing investment because it can help increase company profits, brand awareness, website traffic, conversions, and sales. Apart from that, digital marketing can also provide an opportunity for a company to understand consumer behavior more wisely so that it becomes an efficient tool for introducing investment. Currently, Indonesian people can take advantage of several Sharia-based investment instruments or instruments which, of course, have received permits and are registered with the Financial Services Authority (OJK). Then, this investment was strengthened by the legal basis of the Sharia Council or Indonesian Ulema Council (DSNMUI). Sharia investment can contribute directly to reality and optimally in overall economic growth. However, it should be noted that the contribution of sharia investment is fluctuating and has yet to be able to drive the rate of economic growth in Indonesia ideally.